SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON PUSTAKAWAN MENGGUNAKAN METODE ARAS - Heru Sugara; Eka Pratiwi Parapat; Eko Deswin Siringo-ringo; Muhammad Yunus; M. Ali Hanafiah; Yuyun Dwi Lestari (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This research aims to build a Decision Support System (SPK) for the selection of prospective librarians at the Indonesian Business Polytechnic using the ARAS (Additive Ratio Assessment) method. In the era of globalization and advances in information technology, the need for competent librarians is increasingly urgent. The SPK developed aims to assess prospective librarians objectively based on various criteria such as GPA, age, work experience, psychological test scores and interview scores. This research collected data from 10 prospective librarians and applied the ARAS method to normalize and calculate the value of each alternative. The research results show that the best alternative is A1 with a value of 0.94780, followed by A6 and A7 with a value of 0.91508 and 0.87145 respectively. The application of the ARAS method in this SPK provides selection results that are more transparent, objective and efficient, and supports a better decision-making process in the context of librarian selection.